E-learning curriculum development - Ogrizek Biškupić, Ivana (Array, 2012)
Today we are faced with great popularity of e-learning. New hybrid approaches, complementing the best features of the traditional and technological paradigm have emerged in higher education. Hybrid approach, often labeled as blended learning present thoughtful integration of classroom face-to-face learning experiences with online learning experiences. However our students show less motivation in learning especially from electronic sources. They point out time and amount of information which they read on daily basis as main concentration and motivation problem. Analyzing the fact that nowadays students are digital natives and web 2.0 friendly and considering time our students spend on Internet we decided to develop our curriculum. In this paper we describe how we approached integrating creativity as main motivator factor, eliminated writing an essay task and implementing developing visual model instead. These changes, visual approach to blended learning resulted with great success, students motivation and their final results as well.